AKUNTABILITAS PENANGANAN PELANGGARAN PEMILIHAN UMUM (PEMILU) PADA BADAN PENGAWAS PEMILU (BAWASLU) PROVINSI SUMATERA SELATAN TAHUN 2019 - Zahra, Naimatuz; Kariem, Muhammad Qur’anul; Putra, Dwiki Adi (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to evaluate the accountability for handling general election violations at the General Election Supervisory Agency of South Sumatra Province in 2019 using Koppel Theory which includes indicators of transparency, liability, control, responsibility and responsiveness. This research uses a qualitative approach using the case study method to examine the Accountability for Handling General Election Violations at the General Election Supervisory Agency of South Sumatra Province in 2019. Data was collected through in-depth interviews with informants such as the Commissioner of the Violation Handling Division, Head of the Violation Handling Section, and Violation Handling Staff. Apart from that, field observations and analysis of program documents were also carried out to obtain a comprehensive picture. Data was analyzed by Koppel Theory, which includes Transparency, Liability, Control, Responsibility and Responsiveness. The results of this research show that there are many violations of campaign props in all districts/cities in South Sumatra being installed not in accordance with the regulations, such as being installed on trees, electricity poles, crossing bridges, hedges and public facilities which cause damage to aesthetics and the environment, from several These violations were only a few campaign props that were successfully controlled. The conclusion of this research, it can be assessed that the accountability of Bawaslu of South Sumatra Province regarding handling violations in the 2019 election in general is still classified as not having mature accountability, because it still has obstacles that need to be corrected due to the lack of transparency in the process of handling violations, such as a lack of openness in conveying information, as well as in handling campaign props, the results of controlling campaign props are still many that have not been completed.